MODIFIED MEDIUM FOR MICROPROPAGATION OF RECALCITRANT POTATO (SOLANUM TUBEROSUM L.) CULTIVAR KUFRI JYOTI - EP, Venkatasalam (Potato Journal, 2016)
With the objective to improve in vitro response of the recalcitrant potato cultivar Kufri Jyoti, a study was conducted with different concentrations and combinations of NH4NO3, GA3 and NAA. Increasing the concentration of ammonium nitrate alone to (25.79 Mm) was effective over standard MS medium (20.63 mM) for increasing microplant height and number of leaves. Most of the tested concentration of growth regulators was effective in promoting the growth of microplant in relation to height, root length, number of leaves and roots. Based on present study, it was concluded that the in vitro response of recalcitrant cultivar Kufri Jyoti was significantly improved in terms of shoot length, number of leaves, number of nodes and inter nodal length when the ammonium nitrate concentration in the standard MS medium (20.63 mM) was increased (25.79 mM) and supplemented with GA3 (0.58 µM) as well as NAA (0.1 µM). The next higher concentration of ammonium nitrate (30.94 mM) supplemented with GA3 (0.58 µM ) and NAA (0.1 µM) also exhibited statistically at par response in most of the morphological characters but higher concentration (41.25 mM) retarded all the characters. Therefore, to improve the in vitro response of Kufri Jyoti, modified MS medium with increased level of ammonium nitrate (25.79 mM) supplemented with GA3 (0.58 µM) and NAA (0.1 µM) is recommended.